2022
DOI: 10.3390/hydrology9070112
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Variable SWAT Model Calibration Using Satellite-Based Evapotranspiration Data and Streamflow

Abstract: In this study, monthly streamflow and satellite-based actual evapotranspiration data (AET) were used to evaluate the Soil and Water Assessment Tool (SWAT) model for the calibration of an experimental sub-basin with mixed land-use characteristics in Athens, Greece. Three calibration scenarios were performed using streamflow (i.e., single variable), AET (i.e., single variable), and streamflow–AET data together (i.e., multi-variable) to provide insights into how different calibration scenarios affect the hydrolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Similar studies conducted in Morocco [69], in the Myanmar river basin [68], in the Karkheh river basin of Iran [70], and over the continental USA [71] agreed with the findings of this study that multi-variable calibration performs better than the single variable calibration. Another similar study by [72,73] revealed that multi-variable calibration (evapotranspiration + streamflow) streamflow performance was superior to a single calibration strategy.…”
Section: Model Calibration and Validation Using Glofas River Flow And...mentioning
confidence: 89%
“…Similar studies conducted in Morocco [69], in the Myanmar river basin [68], in the Karkheh river basin of Iran [70], and over the continental USA [71] agreed with the findings of this study that multi-variable calibration performs better than the single variable calibration. Another similar study by [72,73] revealed that multi-variable calibration (evapotranspiration + streamflow) streamflow performance was superior to a single calibration strategy.…”
Section: Model Calibration and Validation Using Glofas River Flow And...mentioning
confidence: 89%
“…The Soil and Water Assessment Tool (SWAT) is an open-source model installed in ArcMap software [53] that is used to classify and divide a watershed into subbasins according to the SRTM (digital elevation model), and the hydrologic parameters such as the area, slope, and length of the extracted subbasins are extracted. In SWAT, subbasins are subdivided into hydrologic response units (HRUs) consisting of homogeneous topographical, land use, and soil characteristics [54,55].…”
mentioning
confidence: 99%